Eksplorasi Liturgi Salat Hari Raya dalam Khazanah Manuskrip Kitab Fath Al-Qarib - Muhammad Faza Fadlil Mubarok; Abdul Givari Pratama Amboy; Achmad Diny Hidayatulllah (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Manuscripts hold immense value as precious treasures passed down from our ancestors and scholars. They serve as a bridge between the past and present, offering a rich source of knowledge for contemporary society. This study aims to: (1) ascertain the legal rulings regarding Eid prayers; (2) determine the proper procedures for performing Eid prayers; and (3) identify the recommended practices associated with Eid prayers. Various methods are employed in manuscript research. This study utilizes a combination of textual criticism and popular readings to analyze an ancient manuscript. Additionally, the study draws upon Islamic jurisprudence (fiqih) to examine and reinforce the content of the manuscript. The popular readings used as a reference are found in the book Fathul Qorib by Shaykh Syamsudin. The findings of this study are as follows: (1) the legal rulings regarding attendance at Eid prayers; (2) the proper procedures for performing Eid prayers; and (3) the recommended practices associated with Eid prayers.